The effect of Dipyridamole on transient ischemia - reperfusion injury of the liver - İbrahim ELVERDİ and Sadık ERSÖZ and Zeki DÖŞEYEN and Esra ERDEMLİ and Uğur BENGİSUN and; m GEÇİM and Nusret ARAS (Turkish Journal of Gastroenterology, 2019)
-